How Does the Auditor Orbit the Audit Engagement? The Effects of Audit Firm Rotation on Auditor Independence and Audit Quality - Delia DELIU; Andrei-Marius OLARIU (Communications of International Proceedings, 2023)
Another trip around the sun? The goal of the audit process is to gather enough pertinent audit evidence to allow the auditor to provide an opinion on the financial statements, at the end of the financial year. Hence, the audit report is the most obvious means of communication between the auditor and those who will be using the financial statements. Previous studies have demonstrated that mandatory audit firm rotation has a positive impact on audit quality. The idea behind auditor rotations is that they help to improve audit quality by reducing the likelihood of the auditor becoming too familiar with the client and potentially compromising their independence and objectivity. Over the years, the debate around the effectiveness of auditor rotations in enhancing audit quality has been a topic of interest among researchers, regulators, and practitioners. While some argue that mandatory rotations can lead to increased competition, better accountability, and ultimately improve audit quality, others argue that mandatory rotations can result in negative consequences such as increased costs, loss of valuable knowledge and expertise, and reduced auditor-client relationships. We therefore see a need for further study to look at the substance and use of the improved auditor's report, building on previous studies. Henceforth, this paper aims to summarize the literature on audit firm rotation, with a focus on the Romanian listed firms, and to give an update on current developments in audit reporting in connection to auditor rotation. We also give a brief overview of the different audit opinions that were issued between 2018 and 2021, for the Romanian companies listed on Bucharest Stock Exchange Market. This paper explores the relationship between auditor rotations and audit quality. First, the paper provides an overview of the existing literature on auditor rotations and their potential impact on audit quality. Second, it identifies key factors that may influence the effectiveness of auditor rotations in enhancing audit quality. Ultimately, this paper aims to provide insights that can inform policy decisions and help promote best practices in auditing.
Keywords: mandatory audit firm rotation; audit report; audit quality; auditor independence; Bucharest Stock Exchange Market; Covid19